2016
DOI: 10.5116/ijme.57f8.c468
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of depression and suicidal behaviour among medical students in Portugal

Abstract: ObjectivesTo examine depression and suicidal behaviour and associated factors in a sample of medical students in Portugal. MethodsWe conducted a cross-sectional study design of 456 native Portuguese medical students from the 4th and 5th year at the University of Lisbon. Participants answered a self-report survey including questions on demographic and clinical variables. Statistical analyses were conducted using the chi-square test, with a Monte Carlo simulation when appropriate. ResultsDepression among medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
55
5
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 58 publications
11
55
5
14
Order By: Relevance
“…We found a strong positive association between risk for alcohol abuse and suicide risk. Similar results have been seen in previous studies conducted both in medical students and in college students in general . To begin, we can propose three possible basic explanations.…”
Section: Discussionsupporting
confidence: 85%
“…We found a strong positive association between risk for alcohol abuse and suicide risk. Similar results have been seen in previous studies conducted both in medical students and in college students in general . To begin, we can propose three possible basic explanations.…”
Section: Discussionsupporting
confidence: 85%
“…1,36,[45][46][47][48] The psychiatric literature shows that women present the highest prevalence of depressive and anxiety disorders. 46,49,50 These disorders are linked to the presence of negative emotions and, along with high stress levels, were also more prevalent among female medical students in most studies assessing similar populations, 23,24,45,51,52 but not in all of them. 53 The present study corroborates such a consensus, since it showed that individuals belonging to the female gender presented more negative emotions and less positive emotions.…”
Section: Discussionmentioning
confidence: 99%
“…[3] However, it is more prevalent among medical students compared to the general population, the prevalence of depression ranged from 2.9% to 38.2% of medical students; however, the female students predominantly undergraduates who are in their initial medical studies have more susceptibility. [4] Dentistry in medical schools and colleges is recognized in providing the most stressful environment which often exerts a negative impact on the academic performance as well as on the psychological well-being of the students. [5,6] Education is not only providing the knowledge or building the skills but also to develop a better version of the students and transforming them into excellent and market compatible individuals.…”
Section: Introductionmentioning
confidence: 99%